Isomeric and Hybrid Ferrocenyl/Cyrhetrenyl Aldimines: A New Family of Multifunctional Compounds - Silva-Molina, C; Silva-Molina, C (Royal Society of Chemistry, 2018)
The synthesis and characterization of two novel and isomeric hybrid ferrocenyl/cyrhetrenyl aldimines [(η5-C5H5)Fe{(η5-C5H4)-CHN-(η5-C5H4)}Re(CO)3] (1) and [(η5-C5H5)Fe{(η5-C5H4)-NCH-(η5-C5H4)}Re(CO)3] (2) are reported. Their X-ray crystal structures reveal that both adopt the E form. However, molecules of 1 and 2 differ in the relative arrangement of the "Fe(η5-C5H5)" and "Re(CO)3" units (anti in 1 and syn in 2). This affects the type of intermolecular interactions, the assembly of the molecules and therefore their crystal architecture. Comparative studies of their electrochemical, spectroscopic and photo-physical properties have allowed us to clarify the effect produced by the location of the organometallic arrays (ferrocenyl or cyrhetrenyl) on electronic delocalization, the proclivity of the metals to undergo oxidation and their emissive properties. Theoretical studies based on Density Functional Theory (DFT) calculations on the two compounds have also been carried out in order to rationalize the experimental results and to assign the bands detected in their electronic spectra. The cytotoxic activities of compounds 1 and 2 against human adenocarcinoma cell lines [breast (MCF7 and MDA-MB-231) and colon (HCT-116)] reveal that imine 2 has a greater inhibitory growth effect than 1 and it is ca. 1.8 times more potent than cisplatin in the triple negative MDA-MB 231 and in the cisplatin resistant HCT-116 cell lines. A comparative study of their effect on the normal and non-tumour human skin fibroblast BJ cell lines is also reported. © 2018 The Royal Society of Chemistry.